The Effect of Communication on Employee Performance at The Sidikalang District Office - Abdimar Jahotlen Tamba; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the effect of communication on employee performance at the Sidikalang District Office, Dairi Regency. Effective communication is an important factor in supporting individual and organizational performance, especially in creating good coordination, solving problems, and building trust and harmonious working relationships. This study uses a quantitative approach with a casual associative research design to test the relationship between communication (independent variable) and employee performance (dependent variable). The population of this study was all employees at the Sidikalang District Office, totaling 49 people, who were also the research sample with a saturated sample technique. Data were collected through questionnaires and analyzed using a simple linear regression method with SPSS version 25 software. The results showed that communication had a positive and significant effect on employee performance, with a regression coefficient of 1.143. The t-count value of 7.112 is greater than the t-table of 2.01174, and the significance value of 0.000 <0.05, which indicates that communication statistically significantly affects employee performance. In addition, the Adjusted R Square value of 0.508 indicates that 50.80% of employee performance variability can be explained by communication variables, while the remaining 49.20% is influenced by other factors not studied. This study confirms that good communication, which includes clarity of messages, openness, speed of information delivery, and listening skills, plays an important role in improving employee performance.